2023
DOI: 10.1186/s13613-023-01153-6
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and evidence for the use of new beta-lactam/beta-lactamase inhibitor combinations and cefiderocol in critically ill patients

Abstract: Background Healthcare-associated infections involving Gram-negative bacteria (GNB) with difficult-to-treat resistance (DTR) phenotype are associated with impaired patient-centered outcomes and poses daily therapeutic challenges in most of intensive care units worldwide. Over the recent years, four innovative β-lactam/β-lactamase inhibitor (BL/BLI) combinations (ceftolozane–tazobactam, ceftazidime–avibactam, imipenem–relebactam and meropenem–vaborbactam) and a new siderophore cephalosporin (cefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 254 publications
0
9
0
Order By: Relevance
“…However, none of these trials were restricted to ICU patients, and only the CREDIBLE-CR trial focused on carbapenem-resistant pathogen. Some studies suggest that cefiderocol could be a therapeutic alternative to the current treatments available for managing infections caused by multi-drug resistant (MDR) bacteria in the ICU care setting [ 5 , 6 ]. Therefore, we conducted a retrospective cohort study to evaluate the efficacy and safety of cefiderocol compared to Best Available Therapy in the ICU setting for treating difficult-to-treat Nf-GNB.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these trials were restricted to ICU patients, and only the CREDIBLE-CR trial focused on carbapenem-resistant pathogen. Some studies suggest that cefiderocol could be a therapeutic alternative to the current treatments available for managing infections caused by multi-drug resistant (MDR) bacteria in the ICU care setting [ 5 , 6 ]. Therefore, we conducted a retrospective cohort study to evaluate the efficacy and safety of cefiderocol compared to Best Available Therapy in the ICU setting for treating difficult-to-treat Nf-GNB.…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, single-drug therapies with an aminoglycoside or colistin were considered as adequate when fully active in vitro though the pulmonary diffusion of these agents may be suboptimal with low-dose regimen. Fourth, the outcome effect of combination therapy in pneumonia involving XDR or PDR Gram-negative bacteria could not be appraised due to the very low number of patients infected with such pathogens—dedicated studies are warranted to solve this question, especially with novel β-lactams [ 35 , 42 , 43 ]. Fifth, we compared the hazard of AKI between patients with combination and single-drug therapy; yet, adding a second agent to an effective pivotal drug may cause other antimicrobial-related side-effects that were not investigated in our work [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The doses recommended for different antipseudomonal agents [84,88,128,142,144,145] are listed in Table 2. Dose adjustments in case of renal insufficiency are detailed elsewhere [145].…”
Section: Principles Of Treatmentmentioning
confidence: 99%
“…The doses recommended for different antipseudomonal agents [84,88,128,142,144,145] are listed in Table 2. Dose adjustments in case of renal insufficiency are detailed elsewhere [145]. In patients with VAP, a post hoc analysis of the iDiapason trial, did not found any advantages of the dual active antibiotic therapy in term of mortality, length of mechanical ventilation.…”
Section: Principles Of Treatmentmentioning
confidence: 99%